Knowledge, Attitude and Practices of Mothers towards Exclusive Breastfeeding among mothers attending Young Child Clinic in Mpigi Health Center IV. A Cross-sectional Study - Eko Lokoru , Francis (Student’s Journal of Health Research Africa, 2022)
Background. Exclusive breastfeeding is the situation in which an infant receives only breast milk from his/her mother or wet nurse (healthy nurse with the baby between 2-5 months) for the first six (6) months and no other solids or liquids with exceptions of drops or syrup consisting of vitamins, minerals, supplement or medicine. The study aimed to assess mothers’ knowledge, attitude, and practices towards exclusive breastfeeding among mothers attending a young child clinic in Mpigi health center IV. Methodology. A descriptive cross-sectional quantitative method was used during the study and 40 respondents were selected using a simple random sampling method. Results: The majority of the mothers 95% knew some information about exclusive breastfeeding, 77.5% of the mothers knew that breastfeeding is started immediately after breastfeeding, 80% knew the importance of colostrums, and 95% of mothers were willing to exclusively breastfeed their babies, Majority of mothers 55%, felt uncomfortable when breastfeeding in public while 45% felt comfortable while breastfeeding in public, 34(85%) started breastfeeding within the first hour of birth (62.5%), of those who were giving other feeds had introduced them to the baby between 4-5 month. Conclusion: Mothers had good knowledge, a positive attitude, and poor practices toward exclusive breastfeeding. Recommendation : More comprehensive research should be carried out on factors associated with early initiation of mixed feeds and factors associated with limited knowledge of EBF.